FD‐based detector for medical image watermarking. Issue 10 (10th July 2019) - Kumar, Sumit; Jha, Rajib Kumar
Abstract : In this study, the authors propose a novel technique for medical image watermark detection using the concept of the fractional differentiator (FD). The feature of FD as a non‐linear high‐pass filter helps in watermark detection. In the region of non‐interest, the watermark image has been added in a mid‐band frequency range of the discrete cosine transform coefficients of 8 × 8 different blocks by generating direct spread spectrum sequence. Their scheme produces noise‐free watermarked medical images. Furthermore, they derive the test statistics of the proposed detector, which is characterised by the fractional order q . The average errors in pixels (PEs), peak‐signal‐to‐noise ratio (PSNR), structural similarity index (SSIM) and cross‐correlation coefficient (CC) have been used to quantify the capability of the proposed technique over some state‐of‐the‐art techniques. The proposed technique shows that at a particular value of fractional order q, there is a significant reduction in average PEs. It causes an increment in PSNR, SSIM and CC. The proposed technique is tested on a large number of medical images and it is found that their proposed technique works better or comparable with other state‐of‐the‐art techniques.